ANALISIS KEANDALAN DAN PENENTUAN PERSEDIAAN OPTIMAL SUKU CADANG COMPRESOR TWO STAGE FOR VESSEL IQF DENGAN METODE ABC DAN RELIABILITY DI PT.KELOLA MINA LAUT - Muhammad Amirul Mukmin (Prodi Teknik Industri Universitas Muhammadiyah Gresik, 2017)
The Production process PT. Kelola Mina Laut has often had obstacles of not working operation of production systems ( production stop because of the problem at bottleneck or breakdown ). This happens because the breakage production machine or waiting for engine unit/component ordered and purchased to replace the faulty component. Especially on machine compressor two-stage no 6 for vessel IQF 4 So it required that the optimal inventory control of spare parts. The method used for the determination this component is the ABC classification method and the method Reliability. ABC obtained by the method of classification of class A that is a component Cylinder liner, piston, piston ring, water pump cooling kop and oil pump. From research to get the value of reliability and the optimal amount of spare parts that cylinder liner with 0.005566 reliability value and the rate of failure 0.012. component piston with the reliability value of 0.017 and the rate of failure 0.014. component piston ring with the reliability value of 0.069 and the rate of failure 0.003605. Component water pumps cooling kop with reliability value of 0.04 and the rate of failure 0.001933 and component Oil Pump with reliability value of 0.03 and the rate of failure 0.002274. Component count is required in a year on machine compressor two-stage no 6 for vessel IQF 4 is 4 units Cylinder liner,5 units of pistons, 1 unit piston ring, 1 unit water pump cooling kop and 1 unit oil pump. With this research can save maintenance costs amounting to 29.86% by a margin price of Rp 37,506,700.00